Ectopic expression of an annexin from Brassica juncea confers tolerance to abiotic and biotic stress treatments in transgenic tobacco - Jami, Sravan Kumar (Plant physiology and biochemistry : PPB, 2008)
Plant annexins belong to a multigene family and are suggested to play a role in stress responses. A full-length cDNA for a gene encoding an annexin protein was isolated and characterized from Brassica juncea (AnnBj1). AnnBj1 message levels were regulated by abscisic acid, ethephon, salicylic acid, and methyl jasmonate as well as chemicals that induce osmotic stress (NaCl, Mannitol or PEG), heavy metal stress (CdCl(2)) and oxidative stress (methyl viologen or H(2)O(2)). In order to determine if AnnBj1 functions in protection against stress, we generated transgenic tobacco plants ectopically expressing AnnBj1 under the control of constitutive CaMV 35S promoter. The transgenic tobacco plants showed significant tolerance to dehydration (mannitol), salt (NaCl), heavy metal (CdCl(2)) and oxidative stress (H(2)O(2)) at the seedling stage and retained higher chlorophyll levels in response to the above stresses as determined in detached leaf senescence assays. The transgenic plants also showed decreased accumulation of thiobarbituric acid-reactive substances (TBARS) compared to wild-type plants in response to mannitol treatments in leaf disc assays. AnnBj1 recombinant protein exhibited low levels of peroxidase activity in vitro and transgenic plants showed increased total peroxidase activity. Additionally, the transgenic plants showed enhanced resistance to the oomycete pathogen, Phytophthora parasitica var. nicotianae, and increased message levels for several pathogenesis-related proteins. Our results demonstrate that ectopic expression of AnnBj1 in tobacco provides tolerance to a variety of abiotic and biotic stresses